Developing test cases for RJSC's computerization project - Alam, Mahnoor; Kamal, Kazi Shanaz (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.